Antimicrobial therapy: principles of use. (October 2021) - Edwards, Frances; MacGowan, Alasdair; Macnaughton, Emily
Abstract: Prescribing antimicrobials is different from prescribing other medications, as there are wider repercussions that must be considered. Inappropriate or unnecessary use of antibiotics can lead to the generation of antimicrobial resistance in both the individual and the population. New antibiotic development has not kept up with the development of bacterial resistance, and the judicious use of antibiotics, known as antibiotic stewardship, is a vital tool in combatting the growth of multiresistant organisms. When choosing an antimicrobial agent, the prescriber must consider a myriad of factors, including the spectrum of action, the route of administration and the suspected site of infection. In addition, patient factors such as allergy status, age, renal and liver function and weight must be considered.